Psychological and behavioral effects of genetic risk testing for obesity: a systematic review. (May 2016) - Cheera, Emily K; Klarich, DawnKylee S; Hong, Mee Young
Background: Interest is growing in the use of genetic risk testing for lifestyle-related chronic diseases, including obesity, to promote health behavior change.Objective: A systematic review of the literature was conducted to determine the effects that genetic risk feedback for obesity may have on psychological and behavioral factors influencing weight.Methods: The MEDLINE/PubMed online database was searched using predefined search terms.Results: The studies revealed that risk feedback may increase motivation to improve health behaviors, especially among individuals at higher genetic risk. Overweight and obese individuals seemed to experience additional psychological benefits when provided an external explanation for their weight status.Conclusion: While the psychological benefits are promising, the clinical utility of genetic risk testing for obesity remains uncertain.